Pengabdian Masyarakat (Tematik) Pembinaan Keluarga Sukinah dengan Tema Pencegahan dan Penanggulangan Stunting di Kabupaten Tabanan (Genitri: Jurnal Pengabdian Masyarakat Bidang Kesehatan, 2024)
Stunting is a linear growth disorder, which is associated with malnutrition and chronic infections. Stunted children will experience cognitive deficits that interfere with academic abilities, damage children's long-term performance and hinder their developmental potential. SSGI 2022 data shows that the prevalence of stunting in Indonesia is 21.6% and is still considered high considering the WHO target for stunting prevalence of 14% in 2024. The prevalence of stunting in Bali in 2021 is 10.9%. There needs to be efforts to prevent and overcome stunting through community service programs. The Center for Women, Gender and Children, Institute for Research and Community Service, I Gusti Bagus Sugriwa State Hindu University, Denpasar, organizes stunting prevention efforts through fostering sukinah families which are held in Tabanan district. Participants who took part in this activity were 50 women, both married and unmarried. The material presented in this activity is related to how to make efforts to overcome stunting through developing Sukinah families. Activities are carried out for 1 full day. Measuring the success of activities and material achievements is by conducting a pre-test and post-test. After being given the material, there was an increase in knowledge related to the causes, prevention and management of stunting.
Keywords: Service; Causes; Prevention; Overcoming; Stunting